USING LOGICAL QUESTIONS AND TASKS TO DEVELOP CRITICAL AND CREATIVE THINKING IN PRIMARY SCHOOL STUDENTS - Shodiyeva Jamila Xolboyevna; Ergasheva Gulshoda Amirovna, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article explores the scientific and theoretical aspects of teaching students critical and creative thinking. It analyzes the didactic and methodological aspects of organizing logical questions and tasks to develop students’ critical and creative thinking abilities.